2020
DOI: 10.1128/aac.00084-20
|View full text |Cite
|
Sign up to set email alerts
|

Levonadifloxacin, a Novel Benzoquinolizine Fluoroquinolone, Modulates Lipopolysaccharide-Induced Inflammatory Responses in Human Whole-Blood Assay and Murine Acute Lung Injury Model

Abstract: Fluoroquinolones are reported to possess immunomodulatory activity; hence, a novel benzoquinolizine fluoroquinolone, levonadifloxacin, was evaluated in lipopolysaccharide-stimulated human whole-blood (HWB) and mouse acute lung injury (ALI) models. Levonadifloxacin significantly mitigated the inflammatory responses in an HWB assay through inhibition of proinflammatory cytokines and in the ALI model by lowering lung total white blood cell count, myeloperoxidase, and cytokine levels. The immunomodulatory effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This immunomodulatory finding was corroborated using histopathological evidence that suggested minimal infiltration of neutrophils into the lung tissue by levonadifloxacin after a lipopolysaccharide challenge. This feature may play a role in augmenting the clinical efficacy [17] . Levonadifloxacin has comparable antibacterial activity with other quinolones against Haemophilus influenzae, Klebsiella pneumoniae, and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…This immunomodulatory finding was corroborated using histopathological evidence that suggested minimal infiltration of neutrophils into the lung tissue by levonadifloxacin after a lipopolysaccharide challenge. This feature may play a role in augmenting the clinical efficacy [17] . Levonadifloxacin has comparable antibacterial activity with other quinolones against Haemophilus influenzae, Klebsiella pneumoniae, and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the fact that COVID-19 patients may present with immunosuppression, anti-inflammatory activity of levonadifloxacin involving inhibition of proinflammatory cytokines, as established through nonclinical studies, could potentially offer clinical benefits in terms of early resolution of symptoms and restricting the progression towards severe respiratory disease. 23 The main strength of our study is that it includes data on real-word scenario for COVID-19 management from hospitals across the country and thus, this study provides insights on the use of AMAs in COVID-19 patients. Also, very few studies are reported from India regarding use of antibiotic in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…There is also activity against quinolone-susceptible Gram-negative bacteria including Escherichia coli, Klebsiella pneumoniae, Pseudomonas spp and Acinetobacter spp. Furthermore, after systemic administration, levonadifloxacin has inhibitory action against proinflammatory cytokines 74. Due to their antibacterial and anti-inflammatory properties, they are used topically for the treatment of acne vulgaris and may have a role in the role of ocular rosacea and related lid disease 75.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Furthermore, after systemic administration, levonadifloxacin has inhibitory action against proinflammatory cytokines. 74 Due to their antibacterial and anti-inflammatory properties, they are used topically for the treatment of acne vulgaris and may have a role in the role of ocular rosacea and related lid disease. 75 There are no data regarding its use as a topical ophthalmic medication, but it is a promising candidate.…”
Section: Fluoroquinolonesmentioning
confidence: 99%